2020
DOI: 10.1111/cas.14606
|View full text |Cite
|
Sign up to set email alerts
|

Caprylic acid (C8:0) promotes bone metastasis of prostate cancer by dysregulated adipo‐osteogenic balance in bone marrow

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
(55 reference statements)
0
27
0
Order By: Relevance
“…Another study found that this cytokine upregulated the expression of COX-2, as was also observed with caprylic acid treatment ( 33 ), and macrophage chemoattractant protein (MCP-1) in bone marrow adipocytes ( 31 ). This COX-2 upregulation was further linked to an increase in the production of prostaglandin-2 (PGE-2) by bone marrow adipocytes which was proposed to reciprocally act on PCa to activate pro-survival pathways ( 31 , 33 ). Interestingly, PCa cells co-cultured with bone marrow adipocytes exhibited a reduced sensitivity to docetaxel, a drug used to treat metastatic PCa ( 31 ).…”
Section: Prostate Cancermentioning
confidence: 65%
See 3 more Smart Citations
“…Another study found that this cytokine upregulated the expression of COX-2, as was also observed with caprylic acid treatment ( 33 ), and macrophage chemoattractant protein (MCP-1) in bone marrow adipocytes ( 31 ). This COX-2 upregulation was further linked to an increase in the production of prostaglandin-2 (PGE-2) by bone marrow adipocytes which was proposed to reciprocally act on PCa to activate pro-survival pathways ( 31 , 33 ). Interestingly, PCa cells co-cultured with bone marrow adipocytes exhibited a reduced sensitivity to docetaxel, a drug used to treat metastatic PCa ( 31 ).…”
Section: Prostate Cancermentioning
confidence: 65%
“…Two recent preclinical trials have emphasized the association between an increased number bone marrow adipocytes, volume of BMAT and the progression of PCa cells in the bone marrow niche ( 32 , 33 ). High fat diet, caprylic acid treatment and androgen depletion (castration) enhanced the BMSC-to-adipocyte transition in vitro and in mouse models ( 32 , 33 ). Androgen deprivation therapy (ADT) is a common treatment for prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it remains unclear whether BMAs can dedifferentiate into the same tumor-aiding phenotype as found in other adipose tissues. Regarding overall lipid metabolism, researchers have shown that caprylic acid (C8:0) was increased in prostate cancer patients with diagnosed bone metastases ( 95 ). These results open a novel research avenue to study the various fatty acid-influenced molecular actions in the BMA-tumor cell interplays.…”
Section: Metabolic Role In Bone Metastasismentioning
confidence: 99%